Localized NIR-II laser mediated chemodynamic therapy of glioblastoma. (April 2022) - Pan, Yuanbo; Xu, Canxin; Deng, Hongzhang; You, Qing; Zhao, Chenyang; Li, Yanying; Gao, Qianqian; Akakuru, Ozioma Udochukwu; Li, Juan; Zhang, Jianmin; Wu, Aiguo; Chen, Xiaoyuan
Highlights: Localized NIR-II laser mediated CDT and mild hyperthermia post-craniectomy was used for orthotopic GBM treatment. The nanocatalysts could penetrate partially disrupted BBB and target orthotopic GBM with negligible brain toxicity. The LOD could catalyze the oxidization of intratumoral lactic acid to H2 O2, which further enhanced CDT. Graphical Abstract: The embedding cancer cell membrane proteins allow CLLC nanocatalysts to penetrate BBB and actively target GBM. The lactate oxidase can catalyze the oxidization of intratumoral lactic acid to H2 O2 . PA image-guided NIR-II laser irradiation on brain of mice post-craniectomy can induce mild hyperthermia and enhance localized CDT of orthotopic GBM with negligible brain toxicity. ga1 Abstract: The effectiveness of most glioblastoma (GBM) therapeutic agents is hindered by poor blood-brain-barrier (BBB) penetration. Moreover, these therapeutic agents cannot target GBM even if they cross the BBB, resulting in serious brain toxicity. Here, an in situ strategy to elicit chemodynamic therapy (CDT) of orthotopic GBM using biomimetic CuFeSe2 -LOD@Lipo-CM (CLLC) nanocatalysts which are composed of ultrasmall CuFeSe2 nanocrystals (CFS), lactate oxidase (LOD), and liposome containing GBM cell membrane proteins (Lipo-CM), is reported. The embedding of GBM cell membrane proteins allows CLLC nanocatalysts to penetrate partly disrupted BBB and precisely target GBM due to their excellent homologous targeting and immune escaping abilities. The oxidization of intratumoral lactic acid to H2 O2 and pyruvate by LOD leads to the elevation of in situ H2 O2 content, providing self-supplied H2 O2 for CDT. Meanwhile, the nanocatalysts can initiate Cu + based Fenton-like reaction to convert the H2 O2 into highly harmful OH. The skull above the orthotopic GBM was removed to rescue the loss of NIR-II laser energy. Then, based on high photothermal conversion efficiency of the nanocatalysts, PA imaging-guided NIR-II laser irradiation on brain of mice post-craniectomy can induce in situ mild hyperthermia and enhanced localized CDT of orthotopic GBM with negligible brain toxicity. These results show that this biomimetic nanocatalyst can achieve the localized CDT enhanced by the LOD and NIR-II laser, which could be an alternative treatment for GBM.